PEMANFAATAN PEMETAAN TEMATIK UNTUK ANALISIS KEBOCORAN JARINGAN PIPA DISTRIBUSI DI PDAM DEMAK - Sudarsono, Bambang; Nugraha, Arief Laila (TEKNIK, 2013)
Problems that are often faced by water companies, particularly in PDAM Demak are water leaks in the distribution channel. The problem became a threat resulting considerable loss to PDAM Demak. The problem requires a solution to help the PDAM Demak to analyze the distribution pipelines become more optimal. One method used to solve the pipeline leakage in the distribution network PDAM Demak is doing thematic mapping distribution pipeline represents the actual field conditions. Furthermore the results of thematic mapping is processed through Geographic Information Systems (GIS) can be simulated distribution of water flow conditions to determine the level of water leakage occurs. Simulation results , which is done through software EPANET 2.0, a reference to find out which areas have a tendency to water leaks. The area can be mapped on a thematic map that has been built so as to provide information areas prone to leak water in PDAM Demak. Thematic mapping of distribution pipeline is done by GPS navigation survey. The mapping produces a thematic maps as a basemap for water distribution simulation process. Simulation results illustrate that the village Sidomulyo into areas prone to water leakage with the highest rate of water loss is 24,50% from 44.022 m3of water production in December 2012.